QUALITATIVE & QUANTITATIVE PHYTOCHEMICAL SCREENING AND PROXIMATE COMPOSITION OF BOMBAX BUONOPOZENSE (RED SILK COTTON TREE) STEM-BACK - Edem, B. E.; Khan, M. E.; Ibok, N. U. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2016)
Qualitative & quantitative phytochemical screening and proximate composition of Bombax buonopozense stem was investigated. Nine phytochemicals viz: - alkaloid, carbohydrate, phenols, flavonoids, saponins, tannins, protein, terpenoids, and oxalates were observed. Steroids and glycosides were below detectable limits. Quantitative phytochemical analysis indicated that alkaloid, flavonoid, phenols, tannins and saponins had values of 0.68 g, 0.09 g, 2.35 g, 1.41 g and 1.15 g respectively. The proximate analysis gave high percentage moisture content (55.30%). Carbohydrate and protein were of low values (1.04 % and 6.0% respectively). Ash content was found to be 15.30%, fiber (16.80%)All analyses wereper100g of crude sample.